Mediators of the stimulatory effect of S1P on colonic Na+/K+ ATPase - Maysoon Noureddine; Sawsan Kreydiyyeh (PLoS ONE, 2025)
The Na ⁺ /K ⁺ ATPase, commonly known as the Na ⁺ /K⁺ pump, plays a crucial role in colonic sodium and water transport, inducing diarrhea or constipation. Inflammatory bowel disease is often associated with diarrhea and elevated levels of sphingosine-1-phosphate (S1P), suggesting a potential relationship between the pump and S1P. This study investigated the effects of S1P on colonic Na ⁺ /K ⁺ ATPase using Caco-2 cells as a model and the S1P analogue used in the treatment of multiple sclerosis, FTY720P. The pump activity was assessed by measuring the amount of inorganic phosphate released in the presence and absence of ouabain, an ATPase inhibitor. FTY720P induced an inhibition of Na ⁺ /K ⁺ ATPase at 15 minutes that was studied in a previous work. This inhibition shifted however, to stimulation at 2 hours, an effect that was abolished in the presence of JTE-013, an S1PR2 antagonist, and was replicated by CYM5520, an S1PR2 agonist. Further mechanistic exploration revealed that when PKC, NF-κB, COX, PKA, and PI3K enzymes were inhibited, FTY720P no longer influenced Na ⁺ /K ⁺ ATPase activity, indicating their involvement in the signaling cascade. Additional evidence supporting this pathway came from activators of these kinases and exogenous PGE₂, both of which stimulated the pump. The results indicate that FTY720P stimulates Na ⁺ /K ⁺ ATPase at 2 hours by binding to S1PR2, leading to PKC activation, followed by NF-κB-mediated induction of PGE₂ synthesis. PGE₂ then binds to its EP4 receptors, activating PKA and PI3K, ultimately resulting in an increase in the pump’s activity. These findings will open the door to targeted regulation of these intermediate molecules which could potentially alleviate certain undesirable effects of the drug.